2016
DOI: 10.1016/j.canlet.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Role of the tumor microenvironment in regulating apoptosis and cancer progression

Abstract: Apoptosis is a gene-directed program that is engaged to efficiently eliminate dysfunctional cells. Evasion of apoptosis may be an important gate to tumor initiation and therapy resistance. Like any other developmental program, apoptosis can be disrupted by several genetic aberrations driving malignant cells into an uncontrolled progression and survival. For its sustained growth, cancer develops in a complex environment, which provides survival signals and rescues malignant cells from apoptosis. Recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 81 publications
1
68
0
1
Order By: Relevance
“…It is well accepted that the microenvironment plays critical roles in driving tumorigenesis and dictating tumor progression (45,46). This is especially true for the IDH1 mutation, as one main feature of mutant IDH1 is the generation of the neometabolite D-2HG, which can be secreted into the extracellular compartment (6).…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that the microenvironment plays critical roles in driving tumorigenesis and dictating tumor progression (45,46). This is especially true for the IDH1 mutation, as one main feature of mutant IDH1 is the generation of the neometabolite D-2HG, which can be secreted into the extracellular compartment (6).…”
Section: Discussionmentioning
confidence: 99%
“…Renewed interest in the fact that cancer cells have to reprogramme their metabolism in order to proliferate or resist treatment. It must take into consideration that the ability of tumour cells to adapt their metabolism to the local microenvironment (low oxygen, low nutrients) . This variety of metabolic sources might be either a strength, resulting in infinite possibilities for adaptation and increased ability to resist chemotherapy‐induced death, or a weakness that could be targeted to kill cancer cells …”
Section: Discussionmentioning
confidence: 99%
“…Among the 12 biological processes, apoptotic process1516 and biological adhesion1718 are related to the occurrence, development and metastasis of tumor. Previous studies19 have demonstrated that overexpression of SMP30 suppresses the expression of oncogenes c-myc and Haras, but encourages the expression of tumor suppressor gene p53 in rat hepatoma cell line H4-II-E.…”
Section: Discussionmentioning
confidence: 99%